Effects of IgLON5 Antibodies on Neuronal Cytoskeleton: A Link between Autoimmunity and Neurodegeneration. Issue 5 (27th August 2020) - Landa, Jon; Gaig, Carles; Plagumà, Jesús; Saiz, Albert; Antonell, Ana; Sanchez‐Valle, Raquel; Dalmau, Josep; Graus, Francesc; Sabater, Lidia
Abstract : Anti‐IgLON5 disease is a neurological disorder characterized by autoantibodies against IgLON5 and pathological evidence of neuronal‐specific tau accumulation. Here, we report that patients' IgLON5 IgG, but not other cell‐surface antibodies, disrupt the cytoskeletal organization in cultured rat hippocampal neurons, resulting in dystrophic neurites and axonal swelling. Adsorption of IgLON5 IgG with HEK293 cells expressing IgLON5 abrogated the indicated cytoskeletal changes. These findings, along with an increase of levels of neurofilaments in patients' cerebrospinal fluid, suggest that IgLON5 IgG, unlike other cell‐surface antibodies, disrupts neuronal cytoskeleton maintenance, providing a link between autoimmunity and neurodegeneration. ANN NEUROL 2020;88:1023–1027